The evaluation of selected clinical and biochemical parameters in women with ovarian cancer in a 5-year observation period - Bednarek, Wiesława; Wertel, Iwona; Marzec-Kotarska, Barbara; Ćwiklińska, Alicja; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2011)
Introduction : Ovarian cancer is a neoplasm characterised by considerable mortality. The aim of numerous studies which have been conducted is to determine the impact of clinical and biochemical parameters on ovarian cancer prognosis, survival and treatment. Serum CA 125 is mainly used to monitor treatment, detect recurrence and predict response to chemotherapy. Increased epidermal growth factor receptor (EGFR) cancer tissue expression facilitates cell proliferation, apoptosis inhibition and increase of angiogenesis. Material and methods : A group of 74 patients treated with surgery and chemotherapy due to ovarian cancer were included in the study. The analysis of clinical parameters (age, tumour histology and grading, clinical stage according to FIGO, type of surgery) as well as CA 125 concentration and EGFR cancer tissue expression in relation to 5-year survival rates was performed. Results : 5-year survival rates were significantly related to: histological grading, clinical FIGO stage, the extent of primary surgery and cancer recurrence. The best predictors of increased survival rates in ovarian cancer patients were: high histological grade, low clinical FIGO stage, optimal debulking and no recurrence. Statistical multivariate analysis did not demonstrate the influence of EGFR on 5-year survival rate in ovarian cancer patients. However, the considerable and unequivocal impact of the last result of CA 125 concentration, the extent of surgical treatment, histological diagnosis and clinical FIGO stage, in relation to 5-year survival rate, was demonstrated. Conclusion : The results suggest a considerable and significant impact of CA 125 concentration, histological diagnosis, clinical FIGO stage, and optimal debulking, on the 5-year survival rates of patients with ovarian cancer.